Perancangan Sistem Informasi Manajemen Proyek Portal Berita Desa Kalisari Menggunakan Metode Agile - M. Anton; Firman Jaya; Nur Azizah (Jurnal Informatika Dan Tekonologi Komputer (JITEK), 2026)
The rapid progress of digital transformation has prompted village governments to adopt web-based information systems to increase transparency and public participation. However, many village news portals still face management issues such as unstructured workflows, inconsistent content updates, and a lack of systematic project planning. This study aims to design a Project Management Information System (PMIS) for the Kalisari Village News Portal using the Agile methodology. This research uses a Research and Development approach by adopting a Scrum framework, which includes needs analysis, product backlog formulation, iterative sprint development, system testing, and evaluation. Data was collected through interviews, system observations, and user satisfaction questionnaires. The results show that Agile-based PMIS supports more structured project planning, clearer task distribution, and continuous monitoring of portal development activities. Continuous iterative development and user feedback enable the system to adapt effectively to changing human resource needs and limitations at the village level. The proposed system contributes to improving information governance, operational efficiency, and the quality of village news portal services. This study shows that Agile-based project management is an appropriate and sustainable approach to developing village-scale information.